(untitled) (Epidemiology, Biostatistics, and Public Health, 2025)
Alcohol remains a serious threat to the health and wellbeing of people across the island of Ireland. Ireland introduced legislation to introduce mandatory alcohol warning labels (AWLs) in 2026, although implementation is deferred until 2028. The cross-sectional survey research sought to explore support for AWLs across the island. The remainder of the survey then explored concerns people had with more graphic AWLs, as well as exploring what additional warnings or information people would like to see displayed in AWLs. Responses were gathered from 475 staff members and students at two universities, one located in Ireland and the other in Northern Ireland. A high level of support for the proposed Irish AWLs was noted (77.9%), with support for more graphic cigarette-style AWLs lower at 60.2%. The potential development of graphic AWLs evoked a considerable range of concerns thematically arranged as 1) Children; 2) Desensitisation; 3) Risks Over-played; 4) No Impact; 5) Unpleasant Viewing; 6) Addiction; 7) Trauma Trigger; 8) Stigmatisation; 9) Diverse Warnings. Although overall there is support for AWLs amongst the convenience sample, there remains confusion about the need and intent of AWLs. Further research is therefore recommended.